Assessment of bone morphogenetic protein-7 loaded chitosan/β-Glycerophosphate hydrogel on periodontium tissues regeneration of class III furcation defects - Ahmed M. Badr; Hany K. Shalaby; Mohamed A. Awad; Mohamed A. Hashem (Saudi Dental Journal)
Background: Periodontitis is a long-term, multifactorial inflammatory condition that is triggered by bacterial germs and interacts with the host's immune system. The unique attachment of fibrous tissue between the cementum and bone presents a challenge for periodontal regeneration. Aim: To achieve the lowest optimum dose of BMP-7 that helps in periodontal regeneration, involving newly formed cementum, PDL and bone Materials and methods: Five healthy mongrel dogs were used for the study. A critical class III furcation defect was created using rotating burs. The bone defects (ten defects for each group) were allocated to one of the subsequent groups: (Group 1) control with the surgical defect only. (Group 2) Surgical defect implanted with hydrogel only (CS/β-GP). (Group 3) Surgical defect implanted with CS/BMP-7 (50 ng/ml). (Group 4) Surgical defect implanted with CS/BMP-7 (100 ng/ml). Results: Histomorphometric and H&E analysis revealed a statistically significant difference in bone, PDL, and cementum regeneration defects filled with CS/BMP-7 (100 ng/ml) compared with other groups. Conclusion: The standard effective dose for BMP-7 use in periodontal regeneration is 100 ng/ml.